2016
DOI: 10.1161/jaha.115.003128
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Macrophage Migration Inhibitor Factor Is Elevated in Response to Myocardial Ischemia

Abstract: BackgroundMacrophage migration inhibitory factor (MIF) is a key regulator of inflammatory responses, including in the heart. Plasma MIF is elevated early in the course of acute myocardial infarction. In this study, we hypothesized that plasma MIF may also be increased in acute myocardial ischemia.Methods and ResultsPatients undergoing cardiac stress test (stress nuclear myocardial perfusion scan or stress echocardiography) were recruited. Twenty‐two patients had a stress test indicative of myocardial ischemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
(97 reference statements)
2
5
0
Order By: Relevance
“…According to the findings of this study, the levels of MIF, and hs-CRP increased sig-nificantly in all MI patients compared to the control group, with this finding being in agreement with past research (11)(12)(13). Although the MIF is formed by numerous cell types in the human atherosclerotic plaque (14), myocardium is the main source of circulating MIF because of its high MIF content (15). Unlike many cytokines, MIF could be released rapidly with no need for de novo synthesis due to the constitutive expression of MIF and its storage in intracellular pools (16).…”
Section: Discussionsupporting
confidence: 92%
“…According to the findings of this study, the levels of MIF, and hs-CRP increased sig-nificantly in all MI patients compared to the control group, with this finding being in agreement with past research (11)(12)(13). Although the MIF is formed by numerous cell types in the human atherosclerotic plaque (14), myocardium is the main source of circulating MIF because of its high MIF content (15). Unlike many cytokines, MIF could be released rapidly with no need for de novo synthesis due to the constitutive expression of MIF and its storage in intracellular pools (16).…”
Section: Discussionsupporting
confidence: 92%
“…Animal experiments demonstrated that the main source of MIF in the early phase after myocardial infarction is necrotic cardiomyocytes and its secretion pattern is characterized by direct, massive, and rapid release under ischemic stimulation, which is not dependent on de novo synthesis [ 10 , 18 ]. Fan et al [ 19 ] found that the MIF gene expression levels in cardiomyocytes were 30 times higher than that in skeletal muscle cells. Chan et al [ 3 ] established a mouse coronary occlusion model and found that the MIF content in the damaged myocardium decreased by approximately 40%, and a loss of MIF in the damaged cardiomyocyte was also detected.…”
Section: Discussionmentioning
confidence: 99%
“…White et al explored the role of MIF in mediating inflammatory responses following acute myocardial ischemia and found MIF to be rapidly released from the damaged myocardium into the circulation [88]. Plasma MIF levels also have been reported to be associated with infarct size and the extent of post-infarct cardiac remodeling [89]. Mice with genetic Mif -deficiency were found to be protected from prolonged and severe ischemia reperfusion injury, and this effect was associated with reduced expression of inflammatory cytokines, a decrease in the myocardial infiltration of neutrophils and macrophages, and increased macrophage apoptosis [90].…”
Section: Mif Family Proteins In Myocardial Infarction and Ischemia Rementioning
confidence: 99%